Batch and fixed-bed column studies for the adsorptive removal of methyl orange from water using polyethyleneimine-graphine oxide polymer nanocomposite beads - Nolasco, Jirah Emmanuel T.
Batch and continuous fixed-bed column studies were performed using nanocomposite beads made up of chitosan, polyethyleneimine, and graphene oxide as adsorbents for the removal of methyl orange (MO) in water. Batch adsorption experiments showed that MO removal of more than 85% can be achieved by the beads across a wide pH range. Also, kinetics and equilibrium studies demonstrated that the adsorption data correlated well with pseudo-second order kinetic equation (R²+0.9999) and Toth isotherm model (R²=0.9644), respectively, suggesting a multilayer adsorption with a maximum adsorption capacity of 421.51 mg/g. Batch desorption and regeneration studies showed that NaOH is the best desorption agent and the beads can remove up to 9.16 mg/g even after four cycles. The effects of different operating parameters such as initial MO concentration, bed height, and flow rate were investigated using a continuous fixed-bed column. The breakthrough curves generated were fitted with Adams-Bohart, Thomas, Yoon-Nelson, and Yan et al. models. The results showed that Yan et al. model agreed best with the breakthrough curves having R² as high as 0.9917. Lastly, design parameters for a large-scale adsorption column were determined via scale-up approach using the parameters obtained from column run